Development of Flashcard Media Based on Teams Games Tournament for Civics Education in Elementary Schools - Dewanti, Andini; Nurhasanah, Nina; Sumantri, Mohamad Syarif (Universitas Pendidikan Indonesia, 2024)
This Research and Development (RD) aims to develop flashcard media based on the Teams Games Tournament (TGT) method for Civic Education (PPKn) learning in fourth-grade elementary school. The research employed the Research and Development (RD) methodology with the ASSURE model, consisting of Analyze Learners, State Objectives, Select Methods, Media, and Material, Utilize Media and Material, Require Learner Participation, and Evaluate and Revise. The instruments used in this study included interviews and questionnaires. Product validation was conducted by three experts: a subject matter expert, a media expert, and a language expert. The product testing process involved three stages: one-to-one evaluation, small group testing, and field testing. The results of the study indicated that the subject matter validation achieved a percentage of 93.3% (excellent), media validation reached 94.6% (excellent), and language validation scored 82% (excellent). Furthermore, the three stages of product testing yielded an average percentage of 95% (excellent). Therefore, the flashcard media based on the Teams Games Tournament is considered feasible for use as instructional media for teaching Civic Education on the topic of Indonesia's Independence Struggle History in fourth-grade elementary school.